2012
DOI: 10.21101/cejph.a3726
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Tobacco Smoking and the Belief about Weight Control Effect of Smoking among Hungarian Adolescents

Abstract: SUMMARY Introduction:The relationship between body weight and smoking has been well-documented among adult populations, but the data among youth are inconsistent. This study explores the relationship among social, behavioural, body weight-related factors and adolescent smoking while identifying factors associated with the belief that smoking controls weight.Materials and methods: Baseline data from a three-year, prospective cohort study started in 2009 in Hungary's six metropolitan cities. Randomly selected 6t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
3
23
1
1
Order By: Relevance
“…Therefore, increasing the knowledge of adolescents through health education programs on smoking could lead to a significant reduction in cigarette smoking among adolescents. Previous researches on adolescent smoking behavior have indicated more positive attitude toward smoking, and that smokers tended to be related with an increased likelihood of smoking (26, 27). Similarly, our study indicated that attitude variable was a significant factor in predicting cigarette use.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, increasing the knowledge of adolescents through health education programs on smoking could lead to a significant reduction in cigarette smoking among adolescents. Previous researches on adolescent smoking behavior have indicated more positive attitude toward smoking, and that smokers tended to be related with an increased likelihood of smoking (26, 27). Similarly, our study indicated that attitude variable was a significant factor in predicting cigarette use.…”
Section: Discussionmentioning
confidence: 92%
“…Weight perception and appearance satisfaction are known to be important health-related issues in adolescence, and authors repeatedly indicated the importance of these issues when evaluating potential factors associated with SUM in this age group [28,29,30]. Surprisingly, studies directly investigating these associations are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, smoking is common in occupations in which a lean and thin body is necessary for overall success (i.e., ballet, fashion modeling) [31,32]. This perception is probably reflected to the adolescent population as well [29]. Interestingly, body weight perception and satisfaction with overall physical appearance are oppositely related to harmful alcohol drinking in Bosniak girls (those who are not satisfied with appearance/body weight are less likely to consume alcohol) and Croatian girls (consumption is higher in those less satisfied with physical appearance).…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, se ha encontrado que el grupo social asume que los fumadores son personas más extrovertidas, audaces y socialmente más hábiles, en otros términos, que son populares y aceptados fácilmente en distintos grupos (Penzes, Czégledi, Balázs y Foley, 2012); es decir, que fumar tiene un efecto positivo para el fumador sobre las atribuciones personales, impacta las sociales y refuerza las causales de la conducta de fumar (De la Torre y Godoy, 2004), incluso se refuerza la idea de pérdida de control porque socialmente se considera que es imposible dejar de fumar, pues tarde o temprano ocurre una recaída (Londoño et al, 2011). Estas expectativas acerca del consumo de cigarrillo se agrupan en efectos fisiológicos de la nicotina, imagen social, relajación y facilitación de la interacción social (Londoño et al, 2011).…”
Section: )unclassified